1972
DOI: 10.1002/pssa.2210140139
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscope investigation of the microplastic deformation mechanisms of silicon by indentation

Abstract: The specific features of the dislocation structure, occuring in the vicinity of indentations have been studied using Si single crystals under different conditions of deformation (at temperatures of 20 to 700 °C and loadings of 0.5 to 10 p). It is shown, that the deformation of crystals at temperatures of 350 to 650 °C results in twin formation with {111} twinning plane. Flat defects with {115} habit plane are revealed. They are shown to be platelets of a new phase, which is of the hexagonal structure with c = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0
5

Year Published

1975
1975
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(53 citation statements)
references
References 9 publications
2
46
0
5
Order By: Relevance
“…Because of the small size of these rod-like defects, these authors were unable to determine the habit plane between them and the de silicon matrix. However, because of the similarity of the hexagonal/cubic orientation relationship in the two cases, Tan et al [7] assumed that the implantation-induced defects had the same {115}dc habit plane as the indentation-induced dh silicon reported by Eremenko and Nikitenko [6]. Tan et al [7] further repeated the experiments of the Soviet workers and confirmed all their findings.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Because of the small size of these rod-like defects, these authors were unable to determine the habit plane between them and the de silicon matrix. However, because of the similarity of the hexagonal/cubic orientation relationship in the two cases, Tan et al [7] assumed that the implantation-induced defects had the same {115}dc habit plane as the indentation-induced dh silicon reported by Eremenko and Nikitenko [6]. Tan et al [7] further repeated the experiments of the Soviet workers and confirmed all their findings.…”
Section: Introductionmentioning
confidence: 87%
“…The detection of the dh phase by Eremenko and Nikitenko [6] was viewed with a certain degree of skepticism because of this unusual orientation relationship. and because of extra spots in the diffraction patterns from the highly distorted region around the indentation.…”
Section: Introductionmentioning
confidence: 99%
“…The dh germanium was first observed by Eremenko [29] using the same indentation technique as the one that he had used on silicon [30,31]. The optimum range of indentation temperature for the production of hexagonal Ge was found to be -380-400° C and all the crystallographic data.…”
Section: Hexagonal Gennaniummentioning
confidence: 99%
“…The deformation microstructure consists of twin bands and planar ribbons of hexagonal Si radiating from the area of the indent (6). Although at high pressures silicon forms in several different crystal structures, only the diamond-cubic structure is stable at atmospheric pressure (9,10).…”
Section: Introductionmentioning
confidence: 99%